Analysis of the Impact of Product Quality and Service Quality on Customer Loyalty mediated by Customer Satisfaction on Bubble Tea Drink Brands in Batam - Suyono Saputra; Lilis Cinthya (Yayasan Riset dan Pengembangan Intelektual, 2023)
This objective of this research is to analyse the impact of product and service quality on customer loyalty with customer satisfaction as mediator for bubble tea drink brands in Batam. The factors used in this research include trust, price, and promotion. The population in this research were all bubble tea drink customers that make direct purchase on some bubble tea brands in Batam. The sample in this research was taken by using purposive sampling technique from non-probability sampling method with a result of 294 respondents. In this research, an online questionnaire was distributed to the citizens of Batam to gather data. The findings indicate that trust, service quality and promotion have a negative effect on customer loyalty. Contrarily, price, customer satisfaction, and product quality have a positive effect on customer loyalty. Furthermore, customer satisfaction plays a positive role in mediating the impact of product and service quality on customer loyalty.